Banana weevil, Cosmopolites sordidus (Germar) (Coleoptera: Curculionidae) tests for suspected resistance to carbofuran and dieldrin in Masaka District, Uganda - Gold, C.; Bagabe, M.I.; Ssendege, R. (1999)
Damage by banana weevil, Cosmopolites sordidus (Germar), contributed to the decline and disappearance of highland cooking-bananas (Musa spp., type AAA-EA) from the central region of Uganda. Commercial growers in the southwest use chemical insecticides for the control of the weevil although resistance to dieldrin was suspected as the cause of weevil outbreaks in the mid-1980s. Carborfuran, which replaced dieldrin, has also been reported by some farmers to be ineffective against banana weevil. In this study, banana weevils from three farms in the Masaka District, Uganda, were screened for possible resistance to carbofuran and dieldrin. Test populations of banana weevils were not resistant to carbofuran: LD5o values were 3.3-4.5 times higher for males and 1.3-1.7 times higher for females than those for a reference population assumed to be susceptible. This is within the range of normal variability among field populations. Slopes of probit regression lines were steeper for test populations than those of the reference population, while LD99 values were similar among all populations. Two of the test populations had LD5o values for dieldrin twice that of the reference population, while the third had an LD5o value similar to that of the reference group.